Antifungal Potential of Ethanol Extract of Ketapang (Terminalia catappa L) Leaves in Inhibiting the Growth of Candida albicans ATCC 10231 and Active Compound Profile - Luh Made Ary Somia Vagestini; A.A.S.A Sukmaningsih, Retno Kawuri; Insani, Dinda Nur Malik (JSMARTech: Journal of Smart Bioprospecting and Technology, 2025)
Candida albicans is a pathogenic fungus that causes candidiasis and has developed resistance to several antifungal drugs. Ketapang (Terminalia catappa L.) leaves contain active compounds with antimicrobial properties which can developed as an alternative antifungal agents. This study aimed to analyze the antifungal activity and minimum inhibitory concentration (MIC) of ethanol extract of ketapang leaves against C. albicans ATCC 10231 and identify its active compounds. Antifungal assays and MIC tests were conducted using the well diffusion method. Extract partitioning, column chromatography, and Liquid Chromatography–Mass Spectrometry (LC-MS) were used to identify active compounds. Terminalia catappa leaves extract showed the highest inhibition at 20% concentration with a 20.32 ± 0.39 mm inhibition zone and an MIC of 0.1% with a 9.19 ± 0.04 mm zone. The active compounds were found to be polar. Column chromatography yielded seven fractions, none of which exhibited antifungal activity individually. However, when all fractions were combined, a 14.60 ± 0.35 mm inhibition zone was observed. LC-MS analysis identified nine bioactive compounds, five of which, methoxybenzoic acid, cyanidin, pelargonidin 3,5-di-O-glucoside, pelargonidin 3-(6-p-coumaroyl)glucoside, and adamantane-1-carboxylate, are known for antifungal properties. These findings suggest that ketapang leaf extract holds potential as an antifungal agent against C. albicans ATCC 10231, with its activity relying on the combined effect of its active compounds. Keywords: MIC, pathogen, resistance, synergistic